User class mechanisms for quality of service in network mobility - Noor, R.M.; Edwards, C. (2010)
Network mobility basic support (NEMO BS) protocol was introduced by the IETF and allows a mobile network to move and maintain internet sessions. NEMO BS is an extension of mobile IPv6 where the network keeps its home address whilst it is moving. In crowded environments such as trains, the bottleneck is often between the access link and the mobile network. Prioritizing the traffic and allocating a minimum bandwidth guarantee for each user is crucial in this environment. Due to the limited and variable wireless link bandwidth the resource management in mobile network is a challenging problem. A dynamic QoS provisioning framework is designed to provide traffic differentiation according to a user class. Network Simulator, Ns-2 is used to validate the framework and to understand how the mobile network behaves on varies types of applications.